PENYULUHAN KESEHATAN KEPADA IBU MENYUSUI MENGENAI GIZI SEIMBANG UNTUK MENCEGAH TERJADINYA STUNTING - Andini, Ayu; Hilmi Uly Ul Hidayah; Shafa Salsabila; Delli Yuliana Rahmat (Aptekmas Jurnal Pengabdian pada Masyarakat, 2023)
Many nutritional problems occur when the intake of children under five is not balanced so that it will cause problems with poor growth status. The purpose of this health counseling is to determine the influence of breastfeeding mothers' knowledge regarding balanced nutrition after being given health education. Using a survey research design with quantitative methods and accidental sampling techniques. The target used was breastfeeding mothers as many as 18 respondents in Margamukti Village, North Sumedang District, Sumedang Regency, West Java Province. The results of health counseling activities regarding the level of knowing of breastfeeding mothers obtained pre-test results of 50% (Enough) and after being given health education there was a significant accure of 22.2% with post-test results of 72.2% (Very Good). The conclusion shows that there is an influence after being given health education to breastfeeding mothers regarding balanced nutrition in Margamukti Village